PRODUCTION OF ELASTOMERIC POLYMER FIBER WEB BY ELECTROSPINNING PROCESS - (:unkn) unknown (EGE UNIV, 2011)
There are many of parameters that affect the morphology and diameter of electrospun fiber, such as concentration, viscosity. conductivity, molecular weight, moisture and temperature of environment, applied potential, solution feed rate, collector material and collection type, etc. In this study, elastomeric polymer which can be important for some area such as wound dressing, filtration, etc. has been used for electrospinning process. Three different elastomeric polymer, different solvent type and different production parameters (applied voltage, distance, and feed rate) have been tried for experimental studies. Electrospinibility and morphology/diameter of the electrospun fiber based on the appearance obtained from SEM have been analyzed. It has been seen that Cyclohexane could have better performance in terms of electrospinibility than that's of Toluene. Clogging of needle was decreased, when DMF was replaced with THF. However, diameter of electrospun fiber increased because of high viscosity resulted from use of DMF and high boiling point of DMF. The diameter of electrospun fiber are mostly affected from the change of applied voltage, then distance and feed rate. According to t-test (0.05 level, two tailed), the effect of applied voltage on the diameter of electrospun fiber is statistically significant, the effect of distance and feed rate is not statistically significant
Keywords: Electrospinning; Nano fiber web; Elastomeric polymer; SEM; Morphology-diameter; MORPHOLOGY